Knee extension strenght and vertical jumping performance in nordic combined athletes - Paasuke, M.; Ereline, J.; Gapeyeva, H. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: The purpose of this study was to measure knee extension strength and vertical jumping performance characteristics in nordic combined athletes. METHODS: Unilateral knee extension isometric maximal force (MF) and rate of force development (RFD) were measured by a special dynamometer, and unilateral isokinetic peak torque (PT) at angular velocities of 60 and 180 deg/sec by a Cybex II dynamometer. Maximal squat (SJ) and counter-movement jumps (CMJ) were performed on force platform. Nine nordic combined athletes as the experimental group and 12 untrained male university students as the control group participated. RESULTS: Nordic combined athletes had a greater (p<0.05) absolute and relative (body mass-related) values of knee extension isometric MF and isokinetic PT, isometric RFD as well as jumping height in SJ and CMJ, than controls. The jumping height in CMJ was greater (p<0.05) compared with SJ only in nordic combined athletes. Jumping height in SJ and CMJ correlated significantly (p<0.05) with knee extension isometric RFD (r=0.62-0.83) and isokinetic PT at angular velocity of 60 deg/sec (r=0.70-0.82) in nordic combined athletes and untrained men. No significant correlation was obtained between unilateral knee extension isometric MF and isokinetic PT or vertical jumping height. CONCLUSIONS: The present study demonstrated a markedly higher voluntary maximal and explosive force-generating capacity of the extensor muscles of lower extremities in nordic combined athletes compared with untrained men, which indicates the adaptation to specific explosive type of strength training.